Spatial Distortion in the Film Pompeii 2014: Quantitative Visual Analysis of the Arena’s Architectural Heritage Representation - Mouaki Benani, Moundher (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
The cinema approach to historical authenticity in general is not the major concern, engagement and commercial pressure are the guiding principles. The exaggeration in spatial aspects and hyperreal to create more dramatic scenes is a major tool for filmmakers. This paper uses visual analyses method to reveal spatial distortion in the arena, in Pompeii 2014 movie.